Assessment of the value of plant flexibility in low carbon energy system - Teng,F; Pudjianto,D; Strbac,G; Ferretti,F; Bove,R (2014)
This paper examines the value of flexibility from thermal power plant in the future low carbon energy system. Stochastic scheduling model with rolling planning is performed to calculate the operation cost saving due to improved flexibility. The model optimally schedule energy and ancillary services by explicitly modelling of uncertainties associated with renewable production and generation outage. Various flexibility features are defined and analysed across two representative systems showing that the value of plant flexibility is system specific. Sensitivity studies are carried out to understand the impact of different scheduling methods and carbon taxes on the value of flexibility. This paper also presents the discussion on market reward for flexibility.